Serendipitous and systematic chemoproteomic discovery of MBLAC2, HINT1, and NME1-4 inhibitors from histone deacetylase-targeting pharmacophores - Lechner, Severin; Sha, Shuyao; Sethiya, Jigar Paras; Szczupak, Patrycja; Dolot, Rafal; Lomada, Santosh K.; Sakhteman, Amirhossein; Tushaus, Johanna; Prokofeva, Polina; Krauss, Michael; Breu, Ferdinand; Vögerl, Katharina; et al. (ACS chemical biology, 2025)
Metalloenzyme inhibitors often incorporate a hydroxamic acid moiety to bind the bivalent metal ion cofactor within the enzyme’s active site. Recently, inhibitors of Zn2+-dependent histone deacetylases (HDACs), including clinically advanced drugs, have been identified as potent inhibitors of the metalloenzyme MBLAC2. However, selective chemical probes for MBLAC2, which are essential for studying its inhibitory effects, have not yet been reported. To discover highly selective MBLAC2 inhibitors, we conducted chemoproteomic target deconvolution and selectivity profiling of a library of hydroxamic acid-type molecules and other metal-chelating compounds. This screen revealed MBLAC2 as a frequent off-target of supposedly selective HDAC inhibitors, including the HDAC6 inhibitor SW-100. Profiling a focused library of SW-100-related phenylhydroxamic acids led to identifying two compounds, KV-65 and KV-79, which exhibit nanomolar binding affinity for MBLAC2 and over 60-fold selectivity compared to HDACs. Interestingly, some phenylhydroxamic acids were found to bind additional off-targets. We identified KV-30 as the first drug-like inhibitor of the histidine triad nucleotide-binding protein HINT1 and confirmed its mode of inhibition through a cocrystal structure analysis. Furthermore, we report the discovery of the first inhibitors for the undrugged nucleoside diphosphate kinases NME1, NME2, NME3, and NME4. Overall, this study maps the target and off-target landscape of 53 metalloenzyme inhibitors, providing the first selective MBLAC2 inhibitors. Additionally, the discovery of pharmacophores for NME1-4 and HINT1 establishes a foundation for the future design of potent and selective inhibitors for these targets.